Corrosion Damage Assessment Of Aged Offshore Structures - bin Mustafa, Muhammad Bunyamin (Universiti Teknologi PETRONAS, 2018)

(untitled)
Offshore platform or specifically known as oil rig is a large structure with the ability to extract and process the oil and natural gas. An offshore platform has been built many years ago and there are several of offshore platform that still operating today even it already exceeded the limit of their design life. Mostly each of the offshore platforms has their design life which is 25 years old. Each of the offshore platform will faced the environmental condition such as wave, wind and current. These natural phenomena could lead to many of the problems at the offshore platform. For example wind, wave and current could lead to the decreasing of the fatigue strength at the joint of the jacket structure which is very dangerous to the offshore platform. In order to avoid the decreasing of the fatigue strength, a good welding should be applied to the joint of the jacket structure.